2021
DOI: 10.1002/rra.3924
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies of best management practices in reducing nitrate pollution of the Sebdou River, a semi‐arid Mediterranean agricultural catchment (North Africa)

Abstract: A major problem facing the water sector in Algeria is deteriorating water quality, which is strongly influenced by nutrient inputs to agricultural watersheds. To mitigate the effects of agricultural activities and enhance water quality, this study considered the impact of different best management practices (BMPs) in agriculture. The objective of the research was to evaluate the impacts of various agricultural BMPs on nitrate losses in the Sebdou catchment in north-west Africa using the Soil and Water Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Each measure has a protective degree, with its coefficient determined by how well it minimizes runoff and mitigates erosion causes (Benzougagh et al 2020). Cultivation practices such as contour farming, alternating strips or terraces, reforestation on terraces, and ridging are identified as highly effective soil conservation strategies (Zettam et al 2022). These strategies are evaluated based on the soil loss ratio with specific support on agricultural land compared to the corresponding loss with parallel slope plowing (Zouagui et al 2018).…”
Section: Pratique De Gestion Des Terres Factor (P)mentioning
confidence: 99%
“…Each measure has a protective degree, with its coefficient determined by how well it minimizes runoff and mitigates erosion causes (Benzougagh et al 2020). Cultivation practices such as contour farming, alternating strips or terraces, reforestation on terraces, and ridging are identified as highly effective soil conservation strategies (Zettam et al 2022). These strategies are evaluated based on the soil loss ratio with specific support on agricultural land compared to the corresponding loss with parallel slope plowing (Zouagui et al 2018).…”
Section: Pratique De Gestion Des Terres Factor (P)mentioning
confidence: 99%
“…Water erosion is a natural phenomenon with significant environmental consequences, gradually leading to the removal of the topsoil layer and a reduction in agricultural productivity [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…BMPs are shown to be a successful approach to limit water contamination in various catchments across the world, including those in Spain (Puertes et al 2021), China (Liying et al 2021;Ji et al 2022), North Africa (Zettam et al 2022), and Lithuania (Plunge et al 2022). For instance, Zettam et al (2022) discovered that the largest nitrate reduction would occur if parallel terraces were applied in a semi-arid agricultural catchment, while Plunge et al (2022) found that in Lithuania, TN pollutant reduction can be maximized with BMP's implementation. These results show that the deployment of diverse BMPs can be used to reduce TN, TP and sediment pollution across regions with varying climatic conditions, as demonstrated by different simulations.…”
Section: Introductionmentioning
confidence: 99%